Evaluasi dan Perbaikan User Experience Menggunakan User Experience Questionnaire (UEQ) dan Focus Group Discussion (FGD) pada Situs Web FILKOM Apps Mahasiswa Fakultas Ilmu Komputer Universitas Brawijaya - Shafira Viski Izabal; Ismiarta Aknuranda; Hannifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
FILKOM Apps is a website that gives administrational and academic informations for Faculty of Computer Science Brawijaya University student thesis. In each of interactions with the user, various perceptions could be generated by the student as a user include the negative perceptions towards the website and FILKOM UB as the organizations. In order to reduce problems from all negative perceptions that related to user experience, the evaluation was conducted include the redesigned website interface. The aim of this current study is to find out what problems that can be appeared when using FILKOM Apps by gathering various perceptions using User Experience Questionnaire (UEQ) to measure user experience level of old design and Focus Group Discussion (FGD) to gather perceptions and problems in detail. The first evaluation results each UEQ scale means of old design indicated neutral value and UEQ benchmark in â€œbadâ€ category. Moreover, the major problems and negative perceptions have generated from FGD result as the redesigned of new interface design which focused on evaluation results, measured again and got high enhancement on each UEQ scale means and user experience category level on UEQ benchmark. Besides, by gathered written perceptions of new design results more positive perceptions.